Synthesis of BiOI nanosheet/coarsened TiO2 nanobelt heterostructures for enhancing visible light photocatalytic activity. Issue 36 (22nd March 2016) - Li, Zhanjun; Wang, Meiting; Shen, Jianxing; Zhu, Zhiwen; Liu, Yu
Abstract : BiOI nanosheet/coarsened TiO2 nanobelt heterostructure composites (BiOI/TiO2 CNHs) were prepared via an efficient hydrothermal method. Abstract : For high photocatalytic activity, BiOI nanosheets were deposited on acid-corroded TiO2 nanobelts, where a large number of BiOI nanosheet/TiO2 nanobelt heterojunctions could be built. The structure, morphology and optical properties of the BiOI nanosheet/coarsened TiO2 nanobelt heterostructure composites (BiOI/TiO2 CNHs) were characterized by XRD, XPS, SEM, HRTEM, DRS, PL, TOC and nitrogen sorption. The XRD results show that only two phases of TiO2 and BiOI were found in the composites. The HRTEM image shows clear lattice fringes, which prove the formation of heterojunctions at the interface between BiOI and coarsened TiO2 . The photocatalytic activity of the BiOI/TiO2 CNHs for the degradation of methyl orange under visible-light irradiation was evaluated. The results reveal that the BiOI/TiO2 CNHs exhibited much higher photocatalytic activity compared with coarsened TiO2 nanobelts and pure BiOI nanosheets due to the introduction of BiOI onto the surface of the coarsened TiO2 nanobelts and the formation of heterojunctions. BiOI acts as a visible light photosensitizer in the BiOI/TiO2 CNHs. In addition, the large surface area and matched energy bands of the BiOI/TiO2 CNHs both contribute to enhancing the photocatalytic activity. In addition, the possible mechanism of promotion of the photocatalytic performance of the new heterostructure system is explained.